Mixed reviews on diversity initiatives: toward an institutional change model for Black faculty in engineering and computing - Miles, Monica L.; McGee, Ebony O.; Botchway, Portia (Frontiers in Education, 2024)
US universities aim to enhance diversity in STEM fields by implementing programs to support racially minoritized students. While diversity initiatives are prevalent in STEM departments, many primarily focus on undergraduate education, leaving limited support for STEM graduate students. The federal "Raise the Bar: STEM Excellence for All Students" initiative, launched by the Biden-Harris Administration, underscores the longstanding concern of underrepresentation. The Sloan Foundation addresses this gap through pathways programming for STEM students, emphasizing graduate school and professoriate preparation. This study explores the perspectives of 29 Black engineering and computing faculty on diversity initiatives, considering historical experiences. Using grounded theory, we analyzed participants' views, revealing a racialized diversity management framework. Our findings outline three organizational environments: 1) stagnant commitment to diversity, 2) moderate assimilation expectations for underrepresented populations, and 3) transformational steps towards equity. Insights from participants shed light on the varying effectiveness of efforts to increase Black representation in engineering academia.